Teacher Candidate Dispositions: Perspectives of Professional Expectations. Issue 1 (2nd January 2016) - Wake, Donna; Bunn, Gary
Abstract : This study describes a programmatic effort to examine dispositions perceptions of teacher candidates entering the profession. Study participants included 114 master's level teaching candidates in their first semester of a nontraditional teacher education program. Teacher candidates scored themselves on a department disposition rubric designed to evaluate their professional behaviors and wrote reflective rationales to support their scoring. Results indicated that candidates positioned themselves as no fault, accepts fault, and assigns fault in writing their rationales. These positions were used as lenses to analyze candidates' positioning in relation to the program and faculty expectations. Candidates' disposition performance rationales relied on their novice status, the demands of work and family, and an admitted minimalist approach to some course demands. Insights gained from the study may allow teacher education faculty to better understand and support candidates' dispositional growth and development .